Ultra-old patients and long-term survival after hip fracture: a real-world assessment - Tiso, Debora; Pizzonia, Monica; Giannotti, Chiara; Tagliafico, Luca; Signori, Alessio; Nencioni, Alessio; Monacelli, Fiammetta (Frontiers in Medicine, 2023)
It’s still undetermined whether ultra-old persons, aged >90 years, are able to tolerate hip fracture surgical stress while maintaining their functional reserve, and even fewer studies have investigated the role of frailty on the risk of mortality, disability, or morbidity in the ultra-old. This is a prospective study performed at the Orthogeriatrics Ward of the IRCCS Policlinico San Martino (Genoa, Italy) that consecutively enrolled 205 older adult patients with hip fractures due to low-energy trauma. Namely, 85 patients were categorized as ultra-old, and 120 patients (64–89 years) were the younger control group. Demographic data, perioperative data, and rehabilitation data were collected. Here we estimated the overall survival and related predictive variables in hospitalized ultra-old hip fracture patients based on a methodologically robust frailty stratification (Rockwood 40-item tool). The median OS for the ultra-old was 18.7 months, which also showed a doubled 1-year mortality risk. Our findings assessed that frailty in the presence of malnutrition, delayed verticalization, and post-operative respiratory complications was associated with a two-fold increase in the risk of long-term mortality, irrespective of advanced chronological age in the ultra-old. Although the higher mortality rate in these patients may be related to a priori lower life expectancy, chronological age alone is an insufficient prognostic determinant for unfavorable outcomes. Our multicomponent prognostic score can be used in combination to stratify frailty in the ultra-old for timely screening and to deliver goals of care discussions prior to surgery, potentially targeting new orthogeriatric pathways for the improvement of appropriateness and treatment intensity.